Continuous Versus Intermittent Nebulization of Salbutamol in Acute Severe Asthma - Noor Gul, Mehr Muhammad Imran, Umair Ahmad, Umar Usman, Hafiz Amjad Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Asthma exacerbation is one of the most common causes of hospitalization among children. It was observed that severe asthma exacerbation is increasing in children with asthma. Objectives: The main objective of the study is to find the continuous versus intermittent nebulization of salbutamol in acute severe asthma. Material and methods: This randomized control trial study was conducted pulmonology department of DHQ Hospital Faisalabad and the duration of this study was from January 2019 to July 2019. Data was collected with the permission of ethical committee of hospital. The data was collected through random sampling technique. Patients were allocated by means of random table to receive salbutamol either by continuous or intermittent nebulization. Results: The data was collected from 100 asthma patients of both genders. The mean age of patients continuous nebulization was 34.56±2.34 years and in intermittent nebulization 39.89±4.76 years. Hypoxemia was present in all patients with a mean PaO2 is 198±78 mmHg in continuous nebulization. Demographic and clinical values are presented in table 01. Practical implication: We can easily apply this method in hospital treatment of continuous and intermittent nebulization of salbutamol in acute severe asthma. Conclusion: It is concluded that there is no difference in continuous and intermittent nebulization of salbutamol in acute severe asthma. In this regard, repeated nebulizations of salbutamol at 20-minute intervals should be regarded as almost identical to continuous nebulization. keywords: Nebulization, Intermittent, Patients